Houseal Elected Mayor Pro Tem - Rogers, Ernie (Valdosta Daily Times, 1987)
Rogers, Ernie. "Houseal Elected Mayor Pro Tem," Valdosta Daily Times, 1987-03-06.
1 electronic record (JPG, JP2, PDF), 1 pages. 560133 bytes.
Keywords: Valdosta (Ga.); Electronic records; Elections; African Americans; Civil rights; Politics and government